Entrepreneurship-Based School Management Model to Increase Entrepreneurial Interest of Vocational Education Students at SMK Negeri 5 Padang - Desky, Abdul Habib Arrasyidi; Ganefri, Ganefri; Yulastri, Asmar; Ta’ali, Ta’ali; Effendi, Hansi; Fiandra, Yudha Aditya (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The purpose of this research project is to ascertain how the entrepreneurial-based managerial model that will be applied at SMK Negeri 5 Padang is seen by learners, educators, and administrators, as well as their expectations for how it will boost students' interest in business management. case study methodology combined with qualitative research. Data sources included learners, professionals, and administrator questionnaires at SMK Negeri 5 Padang as well as observation. It is thought that the entrepreneurship-based management approach can foster an environment in the classroom that encourages the growth of an entrepreneurial mindset. However, in order to increase student interest in entrepreneurship, dedication and support from all stakeholders—including better facilities—are required. Students' interest might be piqued in entrepreneurship by implementing a complete management model centered on entrepreneurship and bolstering infrastructure support.